COGNITIVE BEHAVIORAL THERAPY AGE EFFECTS IN CHILD AND ADOLESCENT ANXIETY: AN INDIVIDUAL PATIENT DATA METAANALYSIS. Issue 9 (8th May 2013) - Bennett, Kathryn; Manassis, Katharina; Walter, Stephen D.; Cheung, Amy; Wilansky‐Traynor, Pamela; Diaz‐Granados, Natalia; Duda, Stephanie; Rice, Maureen; Baer, Susan; Barrett, Paula; Bodden, Denise; Cobham, Vanessa E.; et al.
<x xml:space="preserve">Abstract</x> Background Investigations of age effects on youth anxiety outcomes in randomized trials (RCTs) of cognitive behavior therapy (CBT) have failed to yield a clear result due to inadequate statistical power and methodologic weaknesses. We conducted an individual patient data metaanalysis to address this gap. Question Does age moderate CBT effect size, measured by a clinically and statistically significant interaction between age and CBT exposure? Methods All English language RCTs of CBT for anxiety in 6–19 year olds were identified using systematic review methods. Investigators of eligible trials were invited to submit their individual patient data. The anxiety disorder interview schedule (ADIS) primary diagnosis severity score was the primary outcome. Age effects were investigated using multilevel modeling to account for study level data clustering and random effects. Results Data from 17 of 23 eligible trials were obtained (74%); 16 studies and 1, 171 (78%) cases were available for the analysis. No interaction between age and CBT exposure was found in a model containing age, sex, ADIS baseline severity score, and comorbid depression diagnosis (power ≥ 80%). Sensitivity analyses, including modeling age as both a categorical and continuous variable, revealed this result was robust. Conclusions Adolescents who receive CBT in efficacy research studies show benefits comparable to younger children. However, CBT protocol modifications routinely carried out by expert trial therapists may explain these findings. Adolescent CBT protocols are needed to facilitate the transportability of efficacy research effects to usual care settings where therapists may have less opportunity for CBT training and expertise development.